The Influence of Sustainability Report Disclosure as Moderating Variable towards the Impact of Intellectual Capital on Company's Performance - Utama, Anak Agung Gde Satia; Mirhard, Reza Renaldi (International Journal of Economics and Financial Issues, 2016)
The purpose of this paper is to examine the influence of Sustainability Report (SR) disclosure as moderating variable towards the impact of Intellectual Capital (IC) on company's performance based on 21 companies listed in Indonesia Stock Exchange (IDX) and listed in National Center for Sustainability Reporting Chapter Indonesia (NCSR-ID) for the period 2010-2013. This research used Pulic's model of value added intellectual coefficient (VAIC) to determine the intellectual capital of companies. Company's performance is presented as Return on Assets (ROA), Return on Equity (ROE), and Revenue Growth (RG). The required data to calculate the IC and company's performance was obtained from the annual reports while SR disclosure was obtained from sustainability reports. Results from linear regression analysis show that VAIC has positive effects on ROA and ROE. It means high ROA and ROE companies are associated with more VAIC. Aside from that, VAIC does not have effect to RG. Result from moderated regression analysis also show that sustainability report disclosure has positive effects on ROA and ROE, but does not have any influence on RG. Sustainability report disclosure becomes pure moderator on ROA while become quasi moderator on ROE. It means SR disclosure is only as moderating variable on ROA while it can be both independent and moderating variable on ROE. Keywords: Intellectual capital, Company's performance, Sustainability report, Value added intellectual coefficient, Moderating variable JEL Classifications: G32, M41